Pediatric brucellosis in the central mediterranean region of Türkiye: Insights from a single-center experience - Elif Güdeloğlu; Hasan Tezer; Meltem Polat; Nursel Kara Ulu; Nursel Atay Ünal; Volkan Medeni; Sezin Helvacıoğlu Ayyıldız; Emine Yılmaz Orulluoğlu; Tuğba Bedir Demirdağ; Anıl Tapısız (Trends in Pediatrics)
Objective: We aimed to contribute to the literature by presenting the epidemiologic, clinical, and laboratory characteristics of pediatric patients with brucellosis followed up by our clinic.